2019
DOI: 10.21276/ijcmsr.2019.4.4.4
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study on Role of DTI in Brain Tumours

Abstract: Brain tumors are a heterogeneous group of benign and malignant tumors. Preoperative radiological assessment is vital in understanding the extent of disease invasion and planning surgical management. This study is to analyze the role of DTI in assessing the different patterns of white matter involvement in patients with brain tumors. Material and methods: A retrospective study was conducted in thirty patients with brain tumours who had undergone both conventional and diffusion tensor imaging. Based on the imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
(12 reference statements)
1
2
0
Order By: Relevance
“…We had classified brain tumors in this study into benign and malignant groups, the study included 50 patients 44 of them have malignant lesions (88%) of the cases and 6 have benign lesions (12%) of the cases, we found that there was a statistical difference between the two groups, with prevalence of displacement among the benign group and infiltration and disruption among the malignant group with P value <0.05. This in contrary to the effect of edema where there was no significant difference between the two groups, with P value >0.05. that agreed with study done by G. Karthika [11] who found in their study on 30 patients with brain tumors that high grade gliomas were significantly associated with infiltration of the white matter tracts and with S. Panesar [12 ]who reported in their study that meningiomas, tend to displace white matter rather than specifically damage or destroy it while high-grade gliomas, comprised of aberrant neural tissue, may infiltrate white matter tracts, causing a combination of displacement, disruption, or outright destruction of white matter and we agreed with the result of the study of V. Itagiba [13] who found that the displacement pattern was seen in all the types of tumor. Disruption and infiltration patterns were found in glioblastomas multiforme and anaplastic astrocytomas.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We had classified brain tumors in this study into benign and malignant groups, the study included 50 patients 44 of them have malignant lesions (88%) of the cases and 6 have benign lesions (12%) of the cases, we found that there was a statistical difference between the two groups, with prevalence of displacement among the benign group and infiltration and disruption among the malignant group with P value <0.05. This in contrary to the effect of edema where there was no significant difference between the two groups, with P value >0.05. that agreed with study done by G. Karthika [11] who found in their study on 30 patients with brain tumors that high grade gliomas were significantly associated with infiltration of the white matter tracts and with S. Panesar [12 ]who reported in their study that meningiomas, tend to displace white matter rather than specifically damage or destroy it while high-grade gliomas, comprised of aberrant neural tissue, may infiltrate white matter tracts, causing a combination of displacement, disruption, or outright destruction of white matter and we agreed with the result of the study of V. Itagiba [13] who found that the displacement pattern was seen in all the types of tumor. Disruption and infiltration patterns were found in glioblastomas multiforme and anaplastic astrocytomas.…”
Section: Discussionsupporting
confidence: 93%
“…Three hundred white matter tracts were studied in 50 patients in this study and we found that the most common tract that was affected was the Cortico-Spinal Tract that was affected in 39 cases then Superior Longitudinal Fasiculus that was affected in 38 cases, G. Karthika [11] observed that in their study that the Cortico-Spinal tract was the most common tract to be affected.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation